The Influence of Information Diffusion on Interbank Risk Contagion. (26th March 2021) - Li, Zhinan; Shen, Peilong; Liu, Xiaoyuan
Abstract : In this paper, the stylized features of incomplete and asymmetric information in the interbank market leading to banks' precautionary behaviors are introduced. Based on banks' stylized behavioral rules, the influencing mechanism of information diffusion on interbank risk contagion is analyzed, and how the existence of information diffusion and banks' information-obtaining ability influence the interbank risk contagion is verified through computational simulations. The results show that information diffusion can significantly accelerate the process of and magnify the extent and probability of interbank risk contagion, and improving banks' information-obtaining ability could lower the speed and extent of the interbank risk contagion. This paper also finds and explains some special phenomena of rollover risk contagion when information diffusion exists: the saltatory risk contagion, the circular liquidity trap, and the risk discovery of information diffusion.